Self-Concept and Self-Efficacy and the Appreciation of Batik Art in the Visual Arts Subject - Andini, Linda Zuli; Andaryani, Eka Titi (Journal of Education Reseach and Evaluation, 2025)
Art education in elementary schools in Indonesia faces challenges in implementation and student involvement in the learning process. Based on this, the aim of this study is to analyze the relationship between self-concept and self-efficacy in relation to the appreciation of batik artwork in visual arts education at the elementary school level. This research employs a quantitative approach with correlation analysis to test the correlation between variables and art appreciation. The population for this study consists of fifth-grade elementary school students. The sample size was calculated using Slovin's formula, resulting in a total of 100 respondents. The method used for data collection is a questionnaire. The instrument used for gathering data is the questionnaire sheet. Data analysis techniques involve inferential statistics.The results of the analysis show that there is a significant relationship between self-concept and batik art appreciation, with a significance value of less than 0.05 and a constant value of 0.000. Self-concept has a regression coefficient of -0.343 with a significance value of 0.003, indicating a significant negative relationship. Furthermore, self-efficacy has a positive relationship with batik art appreciation, with an R value of 0.303 and an R Square value of 0.092, meaning that approximately 9.2% of the variability in batik art appreciation can be explained by self-efficacy. It is concluded that self-concept and self-efficacy significantly influence the appreciation of batik artwork.